THE POPULATION'S ECONOMIC EDUCATION IN THE ROMANIAN ACTUALITY - Mihaela, SAVU; Dumitru, CIUCUR (Strategii Manageriale, 2014)
This paper aims at to present the essence and the role of economic education related to the natural movement of a functioning market economy in the Romanian actuality. We understand education as an important form of social consciousness in the sense of bipolarity, namely as the premise and the effect at a dynamic microeconomic and macroeconomic level. In this dynamic movement, economic education appears more and more visibly as a new factor of production or as a new dimension of human capital. In our approach we consider several theoretical and methodological axes that allow us to reveal the interdependence of education to the economic and social development, from an emulative or frantic perspective. In this way we treat the evolution of complex phenomena of economic education in terms of public policy, highlighting the need to intensify the decision-making efforts of management and execution, consistent pursuing to link the causes with the effects of economic education in the Romanian actuality.